2009
DOI: 10.1002/ana.21660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epilepsy magnetic source imaging on intracranial electrode placement

Abstract: Objective-Intracranial electroencephalography (ICEEG) with chronically implanted electrodes is a costly invasive diagnostic procedure that remains necessary for a large proportion of patients who undergo evaluation for epilepsy surgery. This study was designed to evaluate whether magnetic source imaging (MSI), a non-invasive test based on magnetoencephalography source localization, can supplement ICEEG by affecting electrode placement to improve sampling of the seizure onset zone(s).Methods-Of 298 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 29 publications
8
115
0
Order By: Relevance
“…In line with previous studies, our study demonstrates that a single tight MEG cluster is a positive indicator of good seizure outcome, whereas patients with a loose MEG cluster or multiple clusters have less favourable outcomes (Oishi et al, 2006;Knowlton et al, 2009;Almubarak et al, 2014). Intuitively, it is believed that a single tight cluster indicates a restricted epileptogenic generator, whereas the presence of a loose cluster or multiple clusters is suggestive of a more extensive and complicated epileptogenic region, which cannot be adequately removed with a restricted focal resection.…”
Section: The Value Of Meg In Guiding Surgical Resectionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with previous studies, our study demonstrates that a single tight MEG cluster is a positive indicator of good seizure outcome, whereas patients with a loose MEG cluster or multiple clusters have less favourable outcomes (Oishi et al, 2006;Knowlton et al, 2009;Almubarak et al, 2014). Intuitively, it is believed that a single tight cluster indicates a restricted epileptogenic generator, whereas the presence of a loose cluster or multiple clusters is suggestive of a more extensive and complicated epileptogenic region, which cannot be adequately removed with a restricted focal resection.…”
Section: The Value Of Meg In Guiding Surgical Resectionsupporting
confidence: 89%
“…In addition, our study highlights the potential danger of ignoring a clearly positive MEG result by not sampling this region with intracranial electrodes to assess its relationship to the epileptogenic generator. Previous studies examined MEG's value in guiding subdural grid and depth electrode placement, and demonstrated that MEG can offer unique, non-redundant information and help identify implantation sites, where other non-invasive methods failed (Mamelak et al, 2002;Sutherling et al, 2008;Knowlton et al, 2009;Agirre-Arrizubieta et al, 2014). Along the same lines, our study demonstrates the additional value of MEG, specifically in patients implanted with SEEG.…”
Section: The Value Of Meg In Guiding Invasive Electrode Implantationsupporting
confidence: 70%
“…The influence of the skull is estimated to be much less important on components of MEG signals than on those of EEG signals (Lau et al 2013), resulting in good spatial properties of MSI in terms of source localization results and source separation . It has been demonstrated that MSI increases the chance that the seizure onset zone is sampled when patients undergo intracranial investigations for presurgical assessment (Knowlton et al 2009). Moreover, MEG and EEG are characterized by distinct sensitivities according to spatial organizations and functional aspects of the generator.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the reported accuracy of sECD is above 75% for the majority of the studies (Knowlton, 2006;Minassian et al, 1999;Stefan, 1993). In addition, MEG was also shown to be valuable for appropriately determining the subsequent icEEG coverage zone (Fischer et al, 2005;Knowlton et al, 2009;Mamelak et al, 2002). Unfortunately, only a few studies report sECD investigation of ICE.…”
Section: Megmentioning
confidence: 91%